2021
DOI: 10.1021/acsomega.0c06056
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Groundwater Resources and Exploitation Potential: A Case from Weifang City of Shandong Province in China

Abstract: With the rapid growth of population and economy, the demand for groundwater resources is also increasing, leading to the exploitation of groundwater in some areas far greater than the recharge, which easily causes a series of environmental geological problems such as groundwater drawdown, water quality deterioration, surface subsidence, and so on. Taking Shouguang water resource in Weifang City, Shandong Province, China, as an example, the water-bearing formation in the study area can be divided into three typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This ground subsidence is a consequence of groundwater exploitation to fulfill the production and residential needs of the local populace. Shouguang City, where the reservoir is situated, lies in an area known for the excessive exploitation of groundwater resources [40][41][42]. In response to this issue, the city has implemented a series of control measures in recent years.…”
Section: Insar Deformation Resultsmentioning
confidence: 99%
“…This ground subsidence is a consequence of groundwater exploitation to fulfill the production and residential needs of the local populace. Shouguang City, where the reservoir is situated, lies in an area known for the excessive exploitation of groundwater resources [40][41][42]. In response to this issue, the city has implemented a series of control measures in recent years.…”
Section: Insar Deformation Resultsmentioning
confidence: 99%
“…The Global Biodiversity Information Facility (GIBF, http:// www.gbif.org), the National Herbarium Resource Centre (NSII, http://www.nsii.ac.cn), the Digital Herbarium of China (http:// www.cvh.org.cn), and related literature (Qu, 2019;Tao, 2021) were searched for the occurrence records of C. retusus, and the information collected was used as distribution data. For the distribution data that were not labeled with precise geographic coordinates but indicated that the collection location was at the township or more precise level, their longitude and latitude were determined by querying their area name using Google Earth.…”
Section: Species Distribution Sample Pointsmentioning
confidence: 99%
“…It is speculated that the reason is that the elevation value of the recharge area is large. The elevation of the contributing region is calculated mainly through the elevation effect of the δD value of atmospheric precipitation in China, or the recharge elevation of the relationship between the δ 18 O value in groundwater and local altitude is calculated in two ways. To reduce the estimation error of geothermal water recharge elevation in the study area, the average value of the two formulas is used as the recharge elevation value in the study area.…”
Section: Origin Of Hot Water In the Study Areamentioning
confidence: 99%